Investigating Fairness in Transactions: Evidence in Belief Systems - Mohamed, Hazik (International Journal of Islamic Economics and Finance (IJIEF), 2019)
Fairness is one of the central institutional pillars of Islamic law, and its inherent legal framework dictates, among other things, clarity and ethical behaviors in all our endeavors. Righteous behaviors form the foundation of fairness and justice. This paper attempts to address deep religious understanding in human behavior for fairness and justice so as to use religious values in productive economic behaviors, like the sharing risk and benefits in mutual agreements.The methodology of this study assesses the behavior of the subject pool (players representative of Muslims and non-Muslims) through the Ultimatum Game that was designed to test fairness and experiment in decision-making to measure fairness in economic transactions and to observe the level of religious-specific acceptance norms. This paper provides an actual behavioral investigation into how people (Muslims and non-Muslims) behave in real life, whether it is in accordance to what their religion prescribes to them or otherwise. In terms of fairness in contracting, non-Muslims performed a little bit better than Muslims but there were significant differences between the primed and unprimed subjects in the Muslim and non-Muslim groups where it was positive for the Muslim group and negative for the non-Muslim group.